Disability and post-traumatic stress symptoms in the Ukrainian General Population during the 2022 Russian Invasion. (18th April 2023) - Kang, Tarandeep S.; Goodwin, Robin; Hamama-Raz, Yaira; Leshem, Elazar; Ben-Ezra, Menachem
Abstract: Aims: Previous research has shown that people with disabilities are disproportionately vulnerable to symptoms of psychological distress after exposure to armed conflict. Past work has also shown that individuals displaced by conflict are at heightened risk of post-traumatic stress. Using a national online sample of Ukrainians in the early weeks of the 2022 Russian invasion, we aim to examine associations between functional disability and symptoms of post-traumatic stress. Methods: We examined the association between levels of functional disability in the Ukrainian population and symptoms of post-traumatic stress during the 2022 Russian invasion of Ukraine. We analysed data from a national sample of 2000 participants from across this country, assessing disability using the 12-item World Health Organization Disability Assessment Schedule (WHODAS-12)(six domains of disability) and the International Trauma Questionnaire assessment of post-traumatic stress disorder (PTSD) symptomatology according to the Eleventh Edition of The International Classification of Diseases (ICD-11). Moderated regression examined the impact of displacement status on the disability–post-traumatic stress relationship. Results: Different domains of disability predicted post-traumatic stress symptoms (PTSSs) to varying extents, with overall disability score significantly associated with PTSSs. This relationship was not moderated by displacement status. Consistent with previous research, females reported higher levels of post-traumatic stress. Conclusions: In a study of a general population during a time of armed conflict, individuals with more severe disabilities were at greater risk of PTSSs. Psychiatrists and related professionals should consider pre-existing disability as a risk factor for conflict-related post-traumatic stress.